ADOPSI DALAM PERSPEKTIF HUKUM PERDATA, HUKUM ADAT DAN HUKUM ISLAM - Syafi'i, Ahmad (Hunafa: Jurnal Studia Islamika, 2007)
One way to protect children is child adoption, which means embracing a child to the family by which there is a legal relationship between the adopter and the adoptee. In Indonesia, adoption is one of the controversial issues in civil, customary, or Islamic law, which have their own characteristics. These laws occur based on the development of societies in different areas where adoption brings about legal consequences, which are different from one place to anotherKata Kunci: Adopsi, hukum perdata, hukum adat, hukum Islam